IMPLEMENTASI E-GOVERNMENT MELALUI SISKEUDES DENGAN MODEL GOVERNMENT TO GOVERNMENT (G2G) DI DESA KEJAPANAN KECAMATAN GEMPOL - Intan Nical Wahyu Tifany; Ilmi Usrotin Choiriyah (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to describe and analyze the implementation of e-government through the village financial system (SISKEUDES) using the government-to-government (G2G) model in Kejapanan Village in the Gempol District of Pasuruan Regency. The study uses a qualitative descriptive method with data collection techniques such as interviews, observations, and documentation. Data analysis uses policy implementation theory consisting of four main variables: environmental conditions, inter-organizational relationships, organizational resources, and the characteristics and capabilities of the agents responsible for implementation. The results indicate that although Kejapanan Village has the infrastructure and human resources to implement SISKEUDES, it still faces obstacles such as system errors, power outages, technical differences between supervising agencies (DPMD and the Inspectorate), and a double workload for operators who are understaffed. Nevertheless, strong internal village collaboration, adaptive leadership, and self-initiative in training village officials are the main strengths that support the system's sustainability. These findings underscore the importance of cross-sectoral synergy, sustained technical support, and regulatory simplification for the successful digitalization of village finances